Pengaruh Asimetri Informasi, Penekanan Anggaran, Komitmen Organisasi dan Ketidakpastian Lingkungan pada Senjangan Anggaran - Regita Naraswari, Putu Ayu; Sukartha, I Made (E-Jurnal Akuntansi; Vol 26 No 2 (2019)DO - 10.24843/EJA.2019.v26.i02.p30, 2019)
The budget is a periodic plan prepared for a certain period. The difference in the amount of budget submitted by subordinates with the best number of estimates from the organization is budgetary slack. The purpose of this study is to provide empirical evidence of the influence of information asymmetry, budget emphasis, organizational commitment and environmental uncertainty on budgetary slack. This research was conducted at the Starry Hotel in Badung Regency. The research instrument used was a questionnaire with data analysis techniques namely multiple linear regression analysis. The sample used was determined by the nonprobability sampling method, namely purposive sampling. Based on the results of this study it was found that information asymmetry, budget emphasis and environmental uncertainty had a positive effect on budgetary slack. While organizational commitment has a negative effect on budgetary slack. Keywords: Slack, asymmetry, emphasis, commitment, uncertainty